Arthroscopic Excision of Intra-Articular Hip Osteoid Osteoma: A Report of 2 Cases - Alexandre H. Nehme; Alaa G. Bou Ghannam; Joseph P. Imad; Fouad C. Jabbour; Ramzi Moucharafieh; Joseph Wehbe (Case Reports in Orthopedics)
Intra-articular osteoid osteoma is uncommon accounting for approximately 12% of all osteoid osteomas. It presents diagnostic and therapeutic challenges since several traumatic or degenerative pathologies of the joint can be simulated with delay in the diagnosis. We report the clinical, radiographic, and histopathological findings in 2 cases of intra-articular osteoid osteoma of the femoral neck and of the acetabulum. Technical aspects of arthroscopic excision and results of surgery are discussed. Arthroscopy allowed complete excision of the osteoid osteomas, with a short postoperative rehabilitation and excellent functional results.